Volunteers in hospice and palliative care : a handbook for volunteer service managers - Doyle, Derek (Oxford University Press, 2002)
This book provides comprehensive, practical guidelines on the responsibilities of those who lead, co-ordinate and manage volunteers in small hospices, large specialist palliative care units, and in general hospitals with palliative care teams. Volunteers are key workers, who often perform difficult and always important work. In the United Kingdom alone, there are thousands of volunteers in hospice work, a small proportion doing work with patients, and the vast majority doing equally valuable work such as driving, sitting with relatives, manning charity shops and telephones. As a result, Europe, Australia, the United States and Canada are very interested in the United Kingdom's use of volunteers. Aimed primarily at Volunteer Service Managers in small hospices, large specialist palliative care units, and in general hospitals with palliative care teams, this book covers volunteer selection, training, supervision and support, and legal and ethical considerations. Information is presented in an easily accessible way, using key points, summary panels and checklists.; Contributors, who are all Volunteer Service Managers themselves, have included small, clinical vignettes to bring the text to life. This book will also appeal to the volunteers themselves.